5.5k views
3 votes
Simplify.
x 3 ÷ x 5
x2
x8
x-8
x-2

User Dorr
by
6.1k points

2 Answers

3 votes

Answer:

x^-2= 1/x^2

Explanation:

x^3/x^5= x^(3-5)=x^(-2)= 1/x^2

User Carraua
by
6.1k points
3 votes

Answer: Last Option


(x^3)/(x^5)=x^(-2)

Explanation:

We have the following expression:

x³ ÷ x⁵

This is:


(x^3)/(x^5)

To simplify the expression, use the power division of the same base property

Remember that:


(x^m)/(x^n)=x^(m-n)

Then we have that:


(x^3)/(x^5)=x^(3-5)


x^(3-5)=x^(-2)

Finally:


(x^3)/(x^5)=x^(-2)

The answer is the last option

User Nate Flink
by
6.0k points